2019
DOI: 10.1136/bmjopen-2018-027185
|View full text |Cite
|
Sign up to set email alerts
|

Association between LKB1 expression and prognosis of patients with solid tumours: an updated systematic review and meta-analysis

Abstract: ObjectivesLiver kinase B1 (LKB1) is considered a tumour suppressor that can control cell growth and metabolism. Whether LKB1 expression levels are related to clinicopathology and prognosis is controversial. This review aimed to quantitatively examine the latest evidence on this question.DesignAn updated systematic review and meta-analysis on the association between LKB1 expression and prognosis of patients with solid tumours were performed.Data sourcesEligible studies were identified through literature searche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
6
0
Order By: Relevance
“…Furthermore, the loss of LKB1 was associated with an increased risk of recurrence and death in patients with resected colon cancer [ 42 ]. Patients with low LKB1 expression had significantly worse tumor differentiation, larger tumors, early lymph node metastasis, advanced TNM stage, and poor treatment response [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the loss of LKB1 was associated with an increased risk of recurrence and death in patients with resected colon cancer [ 42 ]. Patients with low LKB1 expression had significantly worse tumor differentiation, larger tumors, early lymph node metastasis, advanced TNM stage, and poor treatment response [ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…A marginal association was found between STK11 Mut or KEAP1 Mut (p = 0.079) and the novo brain metastasis. Current data shows that STK11 mutations induce tumor microenvironment changes that promote angiogenesis and recruit an immunosuppressive cell infiltrate [31,32] Moreover, STK11 alterations have been associated with poor tumor differentiation, increased invasive capacity, early lymph node metastasis, and advanced TNM stage [33]. All the molecular processes facilitated by STK11 mutations increase the invasiveness of lung cancer cells and promote colonization of distant sites, which could explain the early development of brain metastasis found in association with mutation in STK11.…”
Section: Discussionmentioning
confidence: 99%
“…[37] A previous study has provided certain information regarding the prognostic value of LKB1 in patients with solid tumours. [38,39] However, no meta-analysis have been performed to evaluate the prognostic value of LKB1 expression in lung cancer. This meta-analysis is aimed to investigate the effect of LKB1 expression on the prognosis and clinicopathological characteristics in lung cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the data have indicated that LKB1 mutation in NSCLC conferred enhanced radio sensitization in combination with trametinib, suggesting LKB1 mutation as a biomarker for patient's trametinib and radiotherapy combination therapy [37] . A previous study has provided certain information regarding the prognostic value of LKB1 in patients with solid tumours [38,39] . However, no meta-analysis have been performed to evaluate the prognostic value of LKB1 expression in lung cancer.…”
Section: Discussionmentioning
confidence: 99%